Mapping Ammonium Flux Across Bacterial Porins: A Novel Electrophysiological Assay with Antimicrobial Relevance - Ishan Ghai (Applied Sciences, 2025)
This study presents a quantitative electrophysiological method to directly measure the passive transport of ammonium ions through bacterial outer membrane porins. Using a zero-current reversal potential assay in planar lipid bilayers under defined bi-ionic gradients, this study evaluates the permeability of ammonium salts through two general diffusion porins: Omp-Pst2 from Providencia stuartii and OmpF from Escherichia coli. Under matched ionic conditions, Omp-Pst2 exhibited significantly higher ammonium flux—approximately 6000 ions per second per monomer at a 1 µM gradient—compared to ~4000 ions per second for OmpF. Importantly, the identity of the accompanying anion (chloride vs. sulfate) modulated both the ion selectivity and flux rate, highlighting the influence of counterion interactions on porin-mediated transport. These findings underscore how structural differences between porins—such as pore geometry and charge distribution—govern ion permeability. The method applied here provides a robust framework for quantifying nutrient flux at the single-channel level and offers novel insights into how Gram-negative bacteria may adapt their membrane transport mechanisms under nitrogen-limited conditions. This work not only enhances our understanding of outer membrane permeability to small ions like ammonium, but also has implications for antimicrobial strategy development and biotechnological applications in nitrogen assimilation.